(untitled) (International Journal of Occupational Safety and Health, 2023)
Introduction: Noise pollution is an important health hazard in modern times and traffic policemen and automobile drivers are exposed to unregulated vehicular noise. This study aims to estimate the exposure levels from traffic noise for traffic policemen and automobile drivers and assess their awareness regarding noise pollution and the use of noise prevention measures. Methods: An analytical cross-sectional study was carried out comprising the exposed and the control group with 121 people in each group. Sound level estimation was carried out across 20 traffic intersections in the city at various times to assess the noise levels. All the participants were administered a pretested questionnaire to assess their awareness regarding noise pollution and as well as the use of noise prevention strategies. The chi-square test was used to estimate the difference between the two groups. P <0.05 was considered statistically significant. Results: The noise levels at traffic intersections are above the permitted and acceptable limits. The mean ±SD of sound levels at traffic points range from 76.7±5.8 dB to 83.4±6.3 dB across various traffic intersections. The mean noise level at the traffic intersection was in the high-risk category (81-86dB) in 25% of traffic points while 75% of traffic points had noise levels in the moderate risk (76 - 81dB) category. 88% of the exposed group and 95% of the control group considered noise to be a form of pollution even though they were not aware of all the harmful effects. In practice, only 34% of study participants used some form of hearing protection measures, even though the majority were aware of the need to do so. Conclusion: The noise levels at traffic intersections are high. This is coupled with a lack of adequate use of hearing protective devices which can be detrimental to the inner ear. Frequent awareness programs are necessary to educate the occupationally exposed personnel on proper noise prevention strategies. At the same, time it is necessary to take decisive measures to curb the ever-increasing menace of occupational noise exposure.